The Idea of Presidential Term Limit as an Implicit Unamendable Provision: Gagasan Pembatasan Masa Jabatan Presiden sebagai Implicit Unamendable Provision - Hatim, Ahmad; Harijanti, Susi Dwi; Giri Ahmad Taufik (Jurnal Konstitusi, 2024)
The discourse on amending Article 7 of the 1945 Constitution to extend the presidential term has surfaced on multiple occasions. The author’s hypothesis asserts that such an amendment is not only challenging but fundamentally unfeasible, as it constitutes an implicit unamendable provision. This article examines this hypothesis using a normative juridical method, which involves analyzing legal norms, principles, and doctrines through a positive legal approach. The study concludes that Article 7 of the 1945 Constitution represents an implicit unamendable provision, as evidenced by its historical context, its interrelation with other constitutional provisions, relevant court decisions, and the procedural framework of the constitutional amendment process.